Variation Characteristics and Influencing Factors of Reference Crop Evapotranspiration in Guangdong Province under Climate Change - HUANG Song; DAI Jiaqi; ZHAO Baoshan; LIU Na; LI Hui; CHU Huaping (Renmin Zhujiang)
To explore the temporal and spatial variation characteristics of reference crop evapotranspiration (ET0) in Guangdong Province under climate change and its influencing factors,based on the surface observation data of 37 meteorological stations in Guangdong Province during 1980—2020,the FAO-56 Penman-Monteith method was applied to calculate the daily ET0 of each meteorological station.In addition,this research systematically analyzed the temporal and spatial variation characteristics of ET0 in Guangdong Province and quantitatively studied the influence degree of various meteorological factors on ET0 by using sensitivity and contribution rate analysis methods.The results show that in terms of time scale,the annual average ET0 in Guangdong Province is 1 150 mm,and it shows a significant increasing trend at the rate of 14.84 mm/10a.In terms of spatial scale,ET0 in Guangdong Province shows an increasing trend from north to south,with a variation range of 1 069~1 235 mm.ET0 is more sensitive to relative humidity and temperature than sunshine duration and wind speed.The contribution rate analysis shows that temperature is the dominant factor for ET0 variation in Guangdong Province,followed by sunshine duration,relative humidity,and wind speed.The potential increase in temperature combined with the decrease in relative humidity can lead to higher ET0 and drought events in the future.This study can provide a scientific basis for water resources planning and agricultural irrigation management in Guangdong Province.